2016 23rd International Conference on Pattern Recognition (ICPR) 2016
DOI: 10.1109/icpr.2016.7899842
|View full text |Cite
|
Sign up to set email alerts
|

Compact multi-scale periocular recognition using SAFE features

Abstract: In this paper, we present a new approach for periocular recognition based on the Symmetry Assessment by Feature Expansion (SAFE) descriptor, which encodes the presence of various symmetric curve families around image key points. We use the sclera center as single key point for feature extraction, highlighting the object-like identity properties that concentrates to this unique point of the eye. As it is demonstrated, such discriminative properties can be encoded with a reduced set of symmetric curves. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Their experiments demonstrated that fusing multiple image features improves recognition accuracy. Alonso-Fernandez et al [9] proposed integrating LBP, HOG, SIFT, and SURF at the score level by weighted sum and reported that this method is robust to the distance between the camera and the subject. Park et al [10] proposed integrating gradient orientation, LBP, and SIFT at the score level by weighted sum.…”
Section: Periocular Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their experiments demonstrated that fusing multiple image features improves recognition accuracy. Alonso-Fernandez et al [9] proposed integrating LBP, HOG, SIFT, and SURF at the score level by weighted sum and reported that this method is robust to the distance between the camera and the subject. Park et al [10] proposed integrating gradient orientation, LBP, and SIFT at the score level by weighted sum.…”
Section: Periocular Recognitionmentioning
confidence: 99%
“…Many methods using handcrafted features have been proposed for periocular authentication [3], [7], [8], [9], [10]. However, deep learning, which has recently been shown to be effective, has been demonstrated to greatly improve accuracy [11].…”
Section: Periocular Recognitionmentioning
confidence: 99%
“…Symmetry Patterns based on the Symmetry Assessment by Feature Expansion (SAFE) descriptor [7], which encodes the presence of various symmetric curve families in concentric annular rings around image key-points. We use the sclera center as unique key-point.…”
Section: Periocular Recognition Systemsmentioning
confidence: 99%